PEMBIASAAN TADARUS AL-QUR’AN DALAM MEMBENTUK KARAKTER PESERTA DIDIK - Yunus, Machmud; Silviani, Hilda; Juanda, Ayi (THORIQOTUNA: Jurnal Pendidikan Islam, 2022)
This study aims to determine the effect of habituation to tadarus Al-Qur’an on the character of students at MTsN 3 Ciamis. The method used in this study is a descriptive method through a quantitative approach. The sampling technique used is stratified random sampling. Data collection techniques used are questionnaires, interviews and observation. As well as quantitative data processing is completed by formula Rank Spearmen (). Based on the results of data processing, that the habit of tadarus Al-Qur’an is classified as good, obtained from the average value value () of 61,7 which is on the interpretation scale of 58,14 – 62,52 with goodclassification. While the character of students is classified as good, obtained from the average value () of 60,4 which is on the interpretation scale of 59,06 – 63,08 with good classification. Then the effect of habituation of tadarus Al-Qur’an on the character of students at MTsN 3 Ciamis has a positive and significant effect with high category, it is proven that the interval of = 0,62 are in the interval 0,61 – 0,80 and (4,538) ≥ (1,692). Habituation of tadarus Al-Qur’an effects the character of students by 38,44 %, while the remaining 61,56 % is influenced by other factors not studied, such as heredity, family environment and community environment.